207k views
5 votes
Help please!! You’d have to find it algebraically!

Help please!! You’d have to find it algebraically!-example-1

1 Answer

3 votes

Answer: (-6,-5)

Explanation:

2x - 2y = -2 ............ equation 1

3x - y = -13 ................ equation 2

solving by substitution method

from equation 2 , make y the subject of the formula, we have

y = 3x + 13 .............. equation 3

substitute equation 3 into equation 1 , we have

2x - 2 (3x + 13 ) = -2

2x - 6x - 26 = -2

-4x - 26 = -2

-4x = -2 +26

-4x = 24

x = 24/-4

x = -6

substitute x = -6 into equation 3 to get the value of y , we have

y = 3(-6) + 13

y = -18 +13

y = -5

User Artem Mezhenin
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.